Democratic representation and democratic sanctions. Issue 3 (3rd July 2018) - Fumagalli, Corrado
Abstract : In this paper, I argue that citizens have an entitlement to sanction representatives, but representatives have tools to anticipate this sanction and reconstruct their views in order to anticipate the views of the people they are supposed to represent. I also argue that represented and representatives have an entitlement to sanction democratic representative institutions and practices, but, unless citizens across the spectrum of all representative relationships agree on many fronts, sanctions are likely to violate the democratic requirement that all subjected to a collective decision should not be mere objects of coercion.